Exclusive Breast Feeding To Support The Cognitive Development Of Early Children At The Sungai Tabuk Health Centerexclusive Breast Feeding To Support The Cognitive Development Of Early Children At The Sungai Tabuk Health Center - Suryati Suryati; Pratiwi Puji Lestari (OMNICODE Journal (Omnicompetence Community Developement Journal), 2023)
Exclusive breastfeeding is giving breast milk for six months without any other additional food. Breastfeeding can provide health and benefits to children as well as children's cognitive development. Exclusive breastfeeding during infancy can develop cognitive function because breast milk contains nutrients for child development, especially child brain development. The results of the study revealed that there was an average difference in knowledge about exclusive breastfeeding to support children's cognitive development where knowledge after counseling was higher than knowledge before counseling. In conclusion, providing health education through counseling about exclusive breastfeeding and improving children's cognitive abilities can increase postpartum mothers' knowledge about the effect of exclusive breastfeeding on children's cognitive development.